Efektivitas Model Pembelajaran Kooperatif Tipe Group Investigation Terhadap Peningkatan Keterampilan Proses Sains Siswa Pada Materi Elastisitas Bahan - Yunita Yunita; Yanti Sofi Makiyah (Department of Physics Education, Universitas Mataram, 2021)
The purpose of this study was to determine the effectiveness of the group investigation type cooperative learning model in improving the science process skills of high school students in material elasticity. The research method used was quasi-experimental and the population used was class XI MIPA one of the public high schools in Tasikmalaya district and the sample used was class XI MIPA 4. The results of this study obtained an effect size value of 3.91 and categorized as high. The t-test of science process skills in students obtained tcount of 26.39 and ttable of 2.86 because tcount> ttable then Ho was rejected and Ha was accepted. Thus, it can be concluded that the group investigation type cooperative learning model was effective in improving the science process skills of high school students on the elasticity of the material.